Reflection on Integrating Traditional Chinese Culture into College Counselors to Carry out Ideological and Political Education for College Students - Luo, Binyu (Journal of Theory and Practice of Social Science, 2023)
Since the reform and opening up, with the deepening of exchanges between China and other countries around the world, China's traditional culture has been influenced by the wave of Western social thought from abroad, especially the ideas and values of the new generation in China have been impacted. Universities are one of the channels for the dissemination of cultural awareness in China. The knowledge content contained in traditional culture in ideological and political education is beneficial for enhancing the moral literacy and social responsibility of college students. Therefore, when carrying out ideological and political education work for college students, university teachers should combine it with high-quality traditional Chinese culture, find the connection between the two, and effectively innovate the ideological and political education work in universities.Moutai known as the “national liquor” band of China has a long history. In recent years, the competition among liquor-making enterprises tends to be intense, and a series of policy adjustment has restricted the development of liquor industry to some extent. So the liquor-making enterprises have to shift their operation idea so that they can survive in such fierce market competition. This paper made a thorough understanding of the entire liquor industry and the macro and micro economic environment of Kweichow Moutai Co., Ltd., integrated with the data of the annual reports of the company over the years, and used SWOT analysis, Michael Porter’s Five Forces Model, core competence analysis to expound the experience and strategies of Kweichow Moutai, respectively.